Checklist of the marine and estuarine fishes of Madang District, Papua New Guinea, western Pacific Ocean, with 820 new records - Fricke, Ronald; Allen, Gerald R.; Andréfouët, Serge; Chen, Wei-Jen; Hamel, Mélanie A.; Laboute, Pierre; Mana, Ralph; Hui, Tan Heok; Uyeno, Daisuke (Zootaxa, 2014)
A checklist of the marine and estuarine fishes of Madang District is presented, combining both previous and new records. After the recent PAPUA NIUGINI 2012 expedition, a total of 1337 species in 129 families have been recorded from the region. One species and one family is not native (Cichlidae: Oreochromis mossambicus), but has been introduced. The native fish fauna of Madang therefore consists of 1336 species in 128 families. The largest families are the Gobiidae, Labridae, Pomacentridae, Apogonidae, Serranidae, Blenniidae, Chaetodontidae, Syngnathidae and Muraenidae, Scorpaenidae and Lutjanidae, Myctophidae, Acanthuridae, Scaridae, Holocentridae, Carangidae, Pomacanthidae and Tetraodontidae, and Caesionidae. A total of 820 fish species (61.4 % of the total marine and estuarine fish fauna) are recorded from Madang for the first time. The fish fauna of Madang includes a total of 187 species of transitional waters and 1326 species in marine habitats. A total of 156 species of the marine or estuarine species also occurs in freshwater. Zoogeographically, 1271 species have a wide distribution range, most frequently a broad Indo-West Pacific distribution. Among the remaining species, only 8 are endemic to Madang District. Anthropogenic threats to the fish fauna and habitats of Madang District include extensive fishing in Madang Lagoon, sometimes with destructive fishing practices; the discharge of untreated sewage of human settlements, mining and industrial developments into the lagoon and nearby oceanic habitats; and destruction of mangrove habitats by extensive construction work on the shores. These anthropogenic threats may call for conservation and monitoring measures in the near future.